212k views
3 votes
5x + 3y = 6
-3x - 3y = 6

User Mcrute
by
5.0k points

1 Answer

9 votes

Answer:

(x,y)=(6,-8)

x=6, y=-8

Explanation:

There are many was to answer this question, some are substitution and elimination. I am going to use the substitution method.

Your system of equation is 5x+3y=6 and -3x-3y=6

5x+3y=6

-5x -5x

3y=6-5x

Now you substittion the first equation to the sencond one. It will look like:

-3x-(6-5x)=6

-3x-6+5x=6

2x-6=6

+6 +6

2x=12

Divide both sides by 2 and you get

x=6

Now lets substiton x inot the orgianl equation.

-3(6)-3y=6

-18-3y=6

+18 +18

-3y=24

Divide both sides by -3

y=-8

So, the answer is x=6, y=-8

User Marc Seeger
by
5.6k points